Fracture of a narrow-diameter roxolid implant: clinical and fractographic considerations - Karl, Matthias; Krafft, Tim; Kelly, J. Robert (International Journal of Oral & Maxillofacial Implants, 2014)
Narrow-diameter implants have become popular, as bone augmentation procedures can frequently be avoided. In order to provide implants with sufficient strength, a titanium-zirconium (Ti-Zr) alloy has recently been introduced purportedly showing improved mechanical properties as compared to commercially pure titanium (cpTi). This paper reports on the clinical and fractographic aspects of a fractured Ti-Zr implant, generally considered a rare event.A narrow-diameter Ti-Zr implant was placed in a patient aged 66 years in the area of the maxillary right canine and used to support a removable partial denture retained by cylindrical telescopic crowns placed on the implant and on the maxillary left canine. Eleven months after successful osseointegration, the patient presented with a horizontally fractured implant. The fractured part was retrieved for fractographic analysis.The implant fractured just apical to the abutment screw, where the wall thickness of the implant is minimal. Scanning electron microscopy (SEM) analysis revealed the starting point of the fracture at the palatal aspect of the implant. No fatigue striations could be observed, indicating a brittle fracture atypical for Ti-based alloys.The fractographic observations correlate with the given loading situation, which is characterized by high levels of moment loading being imposed on the implant by a rigidly retained cantilever prosthesis. Mechanical overload going beyond the approved indications for Roxolid implants (Straumann) has to be seen as primary cause for this fracture.
EVALuna2:24817